Neurometabolic Aspects of Sports-Related Concussion - Domínguez, Delfina C.; Raparla, Mrudula (Seminars in Speech and Language, 2014)
Concussion is a transitory brain injury resulting from a blow to the head. Concussion is considered a mild traumatic brain injury (mTBI), which is self-limited. Repetitive mTBI has been associated with chronic, progressive neurologic damage. Extreme biochemical changes occur in neuron cells as a result of mTBI. These metabolic disturbances may reflect the symptoms observed in patients who had concussions. However, it has been difficult to match clinical signs and symptoms. Currently, there is no test to diagnose concussion. Further studies are needed to elucidate the biochemical details of the metabolic cascade and the associated time frame, which will help determine when an athlete can safely return to the game.
Keywords: Mild traumatic brain injury; concussion; chronic traumatic encephalopathy; second impact syndrome